Measurement of the B→D[bar](*)D(*)K branching fractions - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We present a measurement of the branching fractions of the 22 decay channels of the B0 and B+ mesons to D[bar](*)D(*)K, where the D(*) and D[bar](*) mesons are fully reconstructed. Summing the 10 neutral modes and the 12 charged modes, the branching fractions are found to be B(B0→D[bar](*)D(*)K)=(3.68±0.10±0.24)% and B(B+→D[bar](*)D(*)K)=(4.05±0.11±0.28)%, where the first uncertainties are statistical and the second systematic. The results are based on 429 fb−1 of data containing 471×106BB[bar] pairs collected at the Υ(4S) resonance with the BABAR detector at the SLAC National Accelerator Laboratory.